2010
DOI: 10.1021/ml1000454
|View full text |Cite
|
Sign up to set email alerts
|

KSRP/FUBP2 Is a Binding Protein of GO-Y086, a Cytotoxic Curcumin Analogue

Abstract: Bis(arylmethylidene)acetone derivatives are an important class of curcumin analogues that exhibit various biological and pharmacological activities. We herein report that GO-Y086, a biotinylated bis(arylmethylidene)acetone, inhibits cancer cell growth. We also show that GO-Y086 specifically interacts with the nuclear protein KSRP/FUBP2 by covalent modification. GO-Y086 markedly suppresses the expression of the c-Myc protein, which plays an important role in cellular proliferation and whose expression is regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…Curcumin analogue (GO-Y086) is able to bind with nuclear protein KSRP by covalent modification and markedly suppresses c-Myc protein expression. GO-Y086 has been studied for the control of c-Myc expression in colon cancer cell lines (HCT116) ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin analogue (GO-Y086) is able to bind with nuclear protein KSRP by covalent modification and markedly suppresses c-Myc protein expression. GO-Y086 has been studied for the control of c-Myc expression in colon cancer cell lines (HCT116) ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our DCA bearing the same chemical structure can directly bind KH type‐splicing regulatory protein, which is a single‐strand nucleic acid binding protein that affects different species of mRNAs and microRNAs. Preliminary data indicated that GO‐Y078 affects microRNAs, some of which are associated with the regulation of fibronectin expression.…”
Section: Discussionmentioning
confidence: 99%
“…All solvents and chemicals used here were obtained as reagent‐grade quality from commercial suppliers and used without further purification. 2‐(4‐Phenylphenoxy)ethanol (BP‐C2‐OH) and 6‐(4‐phenylphenoxy)hexanol (BP‐C6‐OH) were prepared by similar literature procedure of 2‐phenylethanol. Octakis(propenyl succinicanhydrido)polyhedral octasilicate (OS‐SA) was prepared using a literature method .…”
Section: Methodsmentioning
confidence: 99%